Pergulatan Politik Identitas Partai-partai Politik Islam: Studi tentang PAN, PKB dan PKS - Mayrudin, Yeby Ma’asan; Akbar, M. Chairil (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
This study seeks to conduct a critical analysis of the vision and practice of Political Islam held by the leading Islamic parties in Indonesia, the National Mandate Party (PAN), the National Awakening Party (PKB) and the Prosperous Justice Party (PKS). Strategy and the methods adopted by the three parties are not always based linearly with Islamic style. The analysis will be directed at explaining their adaptive actions and changes in response to the concrete political realities and developments. Political Islam will be placed in the context not only in terms of identity and ideological elements but also in its intersection with efforts to achieve the targets of political power and success in general elections both in a short-term and a long term. The authors believe that the theme of Political Islam is very interesting after observing the phenomenon of national politics especially since 2017. Strengthened Islamic identity sentiment over the past two years through the National Movement of Guarding MUI Fatwa or GNPF-MUI has undeniably attracted more public attention. Political mobilization against the case of blasphemy by the Governor of Jakarta at that time had opened crucial political spaces. Thus, the struggle for identity politics in Indonesia has become more dynamic and further study or research is highly needed. The development of the Islamic party in Indonesia to a certain degree shows the irony and paradox.